Plasma-reduced Co(OH)2 with activated hydrogen evolution and overall water splitting performance. Issue 6 (13th April 2020) - Jiang, Junxiang; Tang, Yuanhao; Dong, Lin; Zhang, Wenhao; Wu, Haobin; Yu, Xin-Yao
Abstract : An Ar/H2 plasma reduction strategy is developed to accelerate the HER and overall water splitting performance of Co(OH)2 . Abstract : A low-temperature and time-efficient plasma reduction strategy is developed to accelerate the hydrogen evolution reaction (HER) and overall water splitting performance of Co(OH)2 . Superior HER activity (a small overpotential of 35 mV at 10 mA cm −2 ) and excellent overall water splitting performance (1.48 V at 10 mA cm −2 ) are achieved.